Analisis Karakter Tokoh Utama Dipha dalam Novel Bandung Menjelang Pagi Karya Brian Khrisna - Andi Mei Saputra; Albertus Purwaka; Misnawati Misnawati; Lazarus Linarto; Hana Pertiwi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study analyzes the character of the main protagonist in the novel Bandung Menjelang Pagi by Brian Khrisna. The research aims to identify the main character's personality traits using the four temperaments, according to Alwisol (2004:176), which include: (1) Melancholic, characterized as perfectionistic; (2) Sanguine, characterized as popular; (3) Choleric, characterized as strong; and (4) Phlegmatic, characterized as peaceful.  The analysis of the main character revealed twenty-seven quotations from the novel Bandung Menjelang Pagi by Brian Khrisna, which were categorized into the four temperaments: (1) Melancholic (M) with six quotations; (2) Sanguine (S) with eight quotations; (3) Phlegmatic (P) with nine quotations; and (4) Choleric (C) with four quotations (note: the original Indonesian abstract incorrectly listed Melancholic twice, but given the context of four types, the last is assumed to be Choleric).The results of the research indicate that the most dominant and describable character trait of Dipha in the novel Bandung Menjelang Pagi is Phlegmatic. The findings from this research reveal aspects of the character's attitude within the novel. By studying and understanding this character, we can learn about the various attitudes and personalities people possess